2014
DOI: 10.4293/108680813x13693422518830
|View full text |Cite
|
Sign up to set email alerts
|

Male Gender Impact on the Outcome of Laparoscopic Cholecystectomy

Abstract: In this study, male gender was found to have no impact on the outcomes of laparoscopic cholecystectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
19
1
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 13 publications
(11 reference statements)
4
19
1
1
Order By: Relevance
“…Similarly, higher proportion of women patients were observed in studies by Bazoua 15%). 22,23,[15][16][17] In the current study, mean age reported in both male and female groups was below 30 years. Our findings are consistent with a study by Al-Mulhim et al that observed patients with mean age of 32.9 years.…”
Section: Discussionmentioning
confidence: 46%
See 2 more Smart Citations
“…Similarly, higher proportion of women patients were observed in studies by Bazoua 15%). 22,23,[15][16][17] In the current study, mean age reported in both male and female groups was below 30 years. Our findings are consistent with a study by Al-Mulhim et al that observed patients with mean age of 32.9 years.…”
Section: Discussionmentioning
confidence: 46%
“…10,11,18 Several research studies have evidenced that higher surgical difficulties experience in men during LC and increased conversion rates as compared to women. [15][16][17][18][19] Despite the availability of enough evidence, a lot of controversy still governs the role of male gender as an independent risk factor for conversion of LC to open surgery. 20 On these grounds, this single institution study was done to analyse the impact of male sex on outcome of LC to prove whether it is an independent risk factor for conversion or not.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[16][17][18] There have been general agreement that, besides the male gender, there are other significant predictors of conversion such as increased age, obesity, thickened gallbladder wall detected in preoperative biliary ultrasound, acute cholecystitis, morbid obesity, a high ASA classification, previous upper intra-abdominal (gastro intestinal) surgery. 3,18 Controversies still exist on risk factors for conversion, and male patients undergoing LC have more surgical difficulties and increased conversion rates than females. 8,9,13,16 Studies report that male patients had advanced gall bladder disease when they seek treatment leading to difficulties in LC.…”
Section: Discussionmentioning
confidence: 99%
“…Ambe PC et al and Bazoua G et al also found similar results for conversion rates in their studies. 7,11 But there are some other studies which suggest that conversion rates are indeed higher in males. 3,4,[12][13][14][15][16] Although conversion to open surgery should not be seen as a complication, as it is done to ensure patient safety usually after a well-considered decision, it is indeed a significant event as it is likely to increase postoperative morbidity and stay.…”
Section: Discussionmentioning
confidence: 99%